Measurement of the Intestinal pH in Mice under Various Conditions Reveals Alkalization Induced by Antibiotics - Kouki Shimizu; Issei Seiki; Yoshiyuki Goto; Takeshi Murata (MDPI AG, 2021)
The intestinal pH can greatly influence the stability and absorption of oral drugs. Therefore, knowledge of intestinal pH is necessary to understand the conditions for drug delivery. This has previously been measured in humans and rats. However, information on intestinal pH in mice is insufficient despite these animals being used often in preclinical testing. In this study, 72 female ICR mice housed in SPF (specific pathogen-free) conditions were separated into nine groups to determine the intestinal pH under conditions that might cause pH fluctuations, including high-protein diet, ageing, proton pump inhibitor (PPI) treatment, several antibiotic treatment regimens and germ-free mice. pH was measured in samples collected from the ileum, cecum and colon, and compared to control animals. An electrode, 3 mm in diameter, enabled accurate pH measurements with a small amount of gastrointestinal content. Consequently, the pH values in the cecum and colon were increased by high-protein diet, and the pH in the ileum was decreased by PPI. Drastic alkalization was induced by antibiotics, especially in the cecum and colon. The alkalized pH values in germ-free mice suggested that the reduction in the intestinal bacteria caused by antibiotics led to alkalization. Alkalization of the intestinal pH caused by antibiotic treatment was verified in mice. We need further investigations in clinical settings to check whether the same phenomena occur in patients.